New switching table for improved direct power control of three-phase PWM rectifier - Baktash, A.; Vahedi, A.; Masoum, Mohammad (Engineers Australia, 2009)
The switching table based direct power control (ST-DPC) of three-phase PWM rectifier is analysed in this paper. The approach for constructing switching tables used in DPC is presented and an improved switching table (IST-DPC) is proposed. The new switching schedule improves the quality of line current and results in better dynamic performances as compared with the conventional switching table (ST-DPC). In addition, the predictive direct power control (PDPC) of three-phase boost rectifi er is presented, and simulation results (in MATLAB/SIMULINK environment) are compared with those generated by ST-DPC and IST-DPC approaches. Advantages and limitations of each control scheme are highlighted and conclusions regarding applications, quality of current waveforms and burden of calculations are presented.